2020
DOI: 10.1037/tra0000875
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and refugee and immigrant youth: A community-based mental health perspective.

Abstract: In this article, we comment on the experience of the Kovler Center Child Trauma Program (KCCTP) following the March 21, 2020, shelter at home order in Chicago due to COVID-19. The KCCTP is a program of Heartland Alliance International that was founded in 2018 to provide community-based mental health and social services to immigrant and refugee youth and families who have experienced trauma. COVID-19 temporarily closed the doors of the center, suspending provision of in-person services in the community, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 10 publications
2
51
0
3
Order By: Relevance
“…The mental health impact of the COVID-19 pandemic and associated restrictions has been well-documented. Migrants may be particularly affected due to pre-existing risk factors (48, 49) and potential exclusion and social isolation (50), and worsening of pre-existing mental health conditions (51, 52); providing remote therapy for these individuals can be challenging (53). In one Canadian study, however, immigrants were found to be less likely to increase negative health behaviours than Canada-born adults (54).…”
Section: Resultsmentioning
confidence: 99%
“…The mental health impact of the COVID-19 pandemic and associated restrictions has been well-documented. Migrants may be particularly affected due to pre-existing risk factors (48, 49) and potential exclusion and social isolation (50), and worsening of pre-existing mental health conditions (51, 52); providing remote therapy for these individuals can be challenging (53). In one Canadian study, however, immigrants were found to be less likely to increase negative health behaviours than Canada-born adults (54).…”
Section: Resultsmentioning
confidence: 99%
“…Results from a population of individuals in low socio-economic conditions, including migrants, detected a significantly lower percentage of users after the adoption of lockdown measures, with fewer subjects attending follow-up visits during the next months [ 1 ], demonstrating the need for a reorganization of mental health services that are addressed to this population. Tailored psychological aid programs for refugees were implemented, based on informative materials about the virus spread and on mental health condition monitoring by means of phone and, when possible, using telemedicine [ 81 ]. This latter resource, despite limitations due to scarce internet access and setting variation, allowed in some cases to continue treatment programs especially in young subjects [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Disruptions in this pandemic era challenge adolescents who witness suffering and death of loved ones, experience physical isolation from peers, lack formal education, and become aware of their uncertain futures (Phelps & Sperry, 2020). Impacts compound for youth of color (Liu & Modir, 2020), violence-affected youth (Endale et al, 2020), LGBTQ+-identified youth (Salerno et al, 2020), and the many youth whose parents have lost their jobs (Phelps & Sperry, 2020). Bio-psycho-social reorganizations heighten adolescents’ vulnerabilities to changing environments, which they perceive with their advanced cognitive and emotional capacities (Amsel & Smetana, 2011).…”
mentioning
confidence: 99%